PENGARUH PENDEKATAN KETERAMPILAN PROSES TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII MTs NEGERI SLEMAN KOTA YOGYAKARTA - Hasti Septia Nurrochma (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
The research was to know the determine science learning outcomes. In comparative term in the research to know the difference science learning outcomes among that students learned in in process skills approach and expository approach. This research did in MTs Negeri Sleman City in academic year 2014/2015. This study was a quasi experiment. The population in the research was 132 students. The sample is taken using the technique of purposive sampling. The amount of research sample is 62 students, VIII D class as experiment class and VIII F class as control class. The data is taken using an instrument of learning result test in the form of multiple choice which has been tested its validity and reliability. The analysis techniques used analysis requirement included disseminate normality test, and variance homogeneity. Descriptively, the result of the study showed that propensity science learning outcomes result, that learned in process skills approach included of a very high category. The students that learned expository approach included the high category. Comparatively, the results showed is a significant difference in science learning outcomes of students who learned with the process skills approach with students that learned expository approach ( t value = 4,128 > t table = 2,000 ) at the 5 % significance level and. That means that the approach of process skills influence on science learning outcomes students grade VIII MTs Negeri Sleman City in academic year 2014/2015.